KETERAMPILAN GURU DALAM PELAKSANAAN PENILAIAN AUTENTIK DI MI PERGURUAN ISLAM GANRA KABUPATEN SOPPENG - Madinah, Hardianti; St. Syamsudduha; Muh. Anwar HM (Prodi PGMI IAI Sahid, 2025)
This research aims to describe teachers' skills in carrying out authentic assessments at MI Perguruan Islam Ganra, Soppeng district. This type of research is quantitative descriptive. This research uses data collection techniques in the form of questionnaires conducted at MI Perguruan Islam Ganra. The population in this study were all 6 MI Perguruan Islam class teachers. Meanwhile, the sample in this study consisted of 6 people using the saturated sampling method. The instruments used are questionnaires and documentation. The data analysis technique used is descriptive statistical analysis. The results of this research indicate that teachers' skills in analyzing the quality of assessment and determining reference criteria still require special attention and need to be improved, this is due to the many components that must be considered simultaneously in authentic assessment and the obstacles in implementing authentic assessments are that teachers have difficulty in describing assessment results, there are many components that must be considered in implementing assessments, teachers' grade recaps are still done manually, and teachers still experience problems in calculating final grades. This shows that the obstacles in implementing authentic assessment still need to be considered.